On a New Class Related to the Subclass of Close-To-Convex Functions - Singh, Gagandeep; Singh, Gurcharanjit (Sarajevo Journal of Mathematics, 2024)
This paper is concerned with a generalized class of analytic functions which is related to the subclass of close-to-convex functions in the open unit disc $E=\{z:|z|<1\}$. The coefficient estimates, distortion theorem, growth theorem, argument theorem, radius of convexity, Fekete-Szegö inequality and inclusion relation for the functions belonging to this class have been established. The results so obtained will provide a new direction in the study of certain new subclasses of analytic functions.